Longitudinal trends in the quality, effectiveness and attributes of highly rated smartphone health apps. Issue 3 (20th April 2020) - Mercurio, Mara; Larsen, Mark; Wisniewski, Hannah; Henson, Philip; Lagan, Sarah; Torous, John
Abstract : Background: While there are numerous mental health apps on the market today, less is known about their safety and quality. This study aims to offer a longitudinal perspective on the nature of high visibility apps for common mental health and physical health conditions. Methods: In July 2019, we selected the 10 top search-returned apps in the Apple App Store and Android Google Play Store using six keyword terms: depression, anxiety, schizophrenia, addiction, high blood pressure and diabetes. Each app was downloaded by two authors and reviewed by a clinician, and the app was coded for features, functionality, claims, app store properties, and other properties. Results: Compared with 1 year prior, there were few statistically significant changes in app privacy policies, evidence and features. However, there was a high rate of turnover with only 34 (57%) of the apps from the Apple's App Store and 28 (47%) from the Google Play Store remaining in the 2019 top 10 search compared with the 2018 search. Discussion: Although there was a high turnover of top search-returned apps between 2018 and 2019, we found that there were few significant changes in features, privacy, medical claims and other properties. This suggests that, although the highly visible and available apps are changing, there were no significant improvements in app quality or safety.